Caribbean: new dynamics in trade and political economy - Bryan, Anthony T. ed. (Univ. of Miami. North-South Centre MiamiUS, 1995)
Reviews the effects of external debt and structural adjustment. Examines the likely benefits and hazards of development options such as trade liberalization, privatization and foreign direct investment. Looks at the external challenges for the Caribbean presented by the possible disappearance of unilateral trade preferences in Europe and North America. Highlights intra-Caribbean relations and integration and projections for the future of hemispheric cooperation.